Student Perceptions of Online Learning During the Covid-19 Pandemic - Pongkendek, Jesi Jecsen; Ahmar, Dewi Satria; Munandar, Haris; Azzajjad, Muhammad Fath (EduLine: Journal of Education and Learning Innovation, 2022)
Due to the COVID-19 pandemic, lectures must be conducted online. This research is a survey research to find out the perception of students in participating in online learning. Survey of Musamus University students in 6 faculties with a total of 262 respondents. Respondents were selected by proportionate stratified random sampling. The instrument used is a questionnaire made in google form with a total of 21 questions. Data analysis was carried out by calculating the percentage of each answer for each question item. Through this research, the results obtained are (1) Students realize online learning is a learning solution during the Covid-19 pandemic; (2) Students are happy with participating in online learning; (3) Students are enthusiastic to complete assignments; (4) Students realize that through the assignment of lecturers their knowledge is increasing; (5) Students find online learning beneficial for them; (6) Students have mastered the use of online learning platforms; (7) Students hope that online learning will no longer be carried out in the future. Students also prefer face-to-face learning compared to blended learning and online learning, but some students have realized that the blended learning model is an alternative in learning that can be applied in the future